2009
DOI: 10.1074/jbc.m109.022905
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Parathyroid Hormone-related Protein Binding to the Parathyroid Hormone Receptor and Design of Conformation-selective Peptides

Abstract: Parathyroid hormone (PTH) and PTH-related protein (PTHrP) are two related peptides that control calcium/phosphate homeostasis and bone development, respectively, through activation of the PTH/PTHrP receptor (PTH1R), a class B G protein-coupled receptor. Both peptides hold clinical interest for their capacities to stimulate bone formation. PTH and PTHrP display different selectivity for two distinct PTH1R conformations, but how their binding to the receptor differs is unclear. The high resolution crystal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
150
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 45 publications
13
150
1
Order By: Relevance
“…Whether such a divergence in binding modes correlates with some of the differences in functional responses that have been observed for the two ligands in cell-based kinetic binding and signaling assays (Dean et al, 2008) is unclear. For both ligands, the guanidinium side-chain makes extensive, mostly polar contacts with a cluster of receptor residues that form a small pocket at the proximal end of the groove Pioszak et al, 2009). The elaborate set of interactions made by the Arg20 side chain is fully consistent with the high level of evolutionary conservation seen for this residue, as arginine is present at this position in all PTH family ligands studied to date (Fig.…”
Section: Parathyroid Hormone Receptors and Their Ligandssupporting
confidence: 56%
See 3 more Smart Citations
“…Whether such a divergence in binding modes correlates with some of the differences in functional responses that have been observed for the two ligands in cell-based kinetic binding and signaling assays (Dean et al, 2008) is unclear. For both ligands, the guanidinium side-chain makes extensive, mostly polar contacts with a cluster of receptor residues that form a small pocket at the proximal end of the groove Pioszak et al, 2009). The elaborate set of interactions made by the Arg20 side chain is fully consistent with the high level of evolutionary conservation seen for this residue, as arginine is present at this position in all PTH family ligands studied to date (Fig.…”
Section: Parathyroid Hormone Receptors and Their Ligandssupporting
confidence: 56%
“…The mode of binding observed for PTHrP was found to be highly similar that for PTH, such that the new structural data combined were fully consistent with and indeed confirmed the prior functional studies that indicated that, despite the glaring sequence variation, the (15-34) domains of PTH and PTHrP bind to the same or at least largely overlapping sites in the receptor (Jüppner et al, 1988;Caulfield et al, 1990). The cocrystal structure thus shows that the PTHrP domain binds as an amphipathic a-helix with ligand residues Phe23, Leu24, and Ile28 along one helical surface forming extensive hydrophobic interactions with receptor residues lining the groove of the ECD (Pioszak et al, 2009). A slight bend, however, is present in the PTHrP helix at position-27, which leads to a modest divergence in the receptor contacts made by the C-terminal portions of the two ligands.…”
Section: Parathyroid Hormone Receptors and Their Ligandsmentioning
confidence: 87%
See 2 more Smart Citations
“…Recent crystal structures of agonist-bound PTH 1 R extracellular domain revealed that the Cterminal hormone residue does not form direct contacts with the receptor [16]. This made possible two recent biotechnological forms of PTH 1-34 -based agonists elongated at their Cterminus, either with a linker and trans-membrane tether in one case [6,7], or in the other, with the green fluorescent protein (GFP), leading to a high molecular weight probe suitable for imaging studies in cells that express recombinant PTH 1 R [3] (schematic representation, Fig.…”
Section: Introductionmentioning
confidence: 99%